Immunoenhancing Enteral and Parenteral Nutrition for Gastrointestinal Surgery: A Multiple-treatments Meta-analysis. Issue 4 (April 2015) - Mazaki, Takero; Ishii, Yukimoto; Murai, Ichiro
Abstract : Objective: Frequentist meta-analyses have demonstrated that immunoenhancing parenteral nutrition (IMPN) and enteral nutrition (IMEN) reduce the incidence of infection and shorten the length of hospital stays compared with standard parenteral nutrition (SPN) and enteral nutrition (SEN). The aim of this study was to evaluate which kind of nutrition—SPN, SEN, IMPN, and IMEN—is most efficacious for reducing the incidence of complications after gastrointestinal surgery. Methods: An English literature search was carried out for randomized controlled trials published from January 1990 to February 2013 that evaluated the clinical efficacy of 4 kinds of nutrition after gastrointestinal surgery. A Bayesian framework was used to calculate the odds ratio between each treatment and the rank order. Results: Seventy-four studies (7572 participants) were included. According to the surface below the cumulative ranking curve (SUCRA) ordering from the best to the worst, IMEN was ranked first for reducing the incidence of 7 complications—any infection (SUCRA = 0.86), overall complication (SUCRA = 0.88), mortality (SUCRA = 0.81), wound infection (SUCRA = 0.79), intra-abdominal abscess (SUCRA = 0.98), anastomotic leak (SUCRA = 0.79), and sepsis (SUCRA = 0.92). Also, IMEN was ranked second for pneumonia and urinary tract infection. IMPN was ranked first for pneumonia (SUCRA = 0.81) and urinary tract infection (SUCRA = 0.86), third for mortality, and fourth for both intra-abdominal abscess and anastomotic leak. SPN showed an inferior efficacy for almost all outcomes. Conclusions: This study suggests that IMEN outperformed other nutrition types for reducing complications and IMEN should be considered the best available option. Abstract : Supplemental Digital Content is Available in the Text.The aim of this study was to evaluate which kind of nutrition is most efficacious for reducing the incidence of complications after gastrointestinal surgery. Immunoenhancing enteral nutrition outperformed other nutrition types and should be considered the best available option.